Antibacterial and dermal toxicological profiles of ethyl acetate extract from Crassocephalum bauchiense (Hutch.) Milne-Redh (Asteraceae) - Njateng Guy SS; Tiabou Alambert T; Koanga Martin M; Lunga Paul K; Ngono Rosalie AN; Mouokeu Raymond S; Tamokou Jean DD; Kuiate Jules-Roger (BMC, 2011)
Abstract Background The emergence in recent years of numerous resistant strains of pathogenic bacteria to a range of formerly efficient antibiotics constitutes a serious threat to public health. Crassocephalum bauchiense, a medicinal herb found in the West Region of Cameroon is used to treat gastrointestinal infections as well as liver disorders. The ethyl acetate extract from the leaves of C. bauchiense was evaluated for its antibacterial activity as well as acute and sub-acute toxicities. Methods The plant extract was prepared by maceration in ethyl acetate. Its phytochemical screening was done by standard methods. The broth microdilution method was used to evaluate the in vitro antibacterial activity. The in vivo antibacterial activity of a gel formulation (0.05, 1 and 2% w/v) of this extract was evaluated using a Staphylococcus aureus-induced dermatitis in a murine model. Selected haematological and biochemical parameters were used to evaluate the dermal sub-acute toxicity of the extract in rats. Results Phytochemical screening of the C. bauchiense extract revealed the presence of alkaloids, phenols, tannins and sterols. In vitro antibacterial activities were observed against all the tested microorganisms (MIC = 0.04-6.25 mg/ml). Formulated extract-gel (2% w/v) and gentamycin (reference drug) eradicated the microbial infection after five days of treatment. A single dermal dose of this extract up to 32 g/kg body weight (bw) did not produce any visible sign of toxicity. Also, daily dermal application of the C. bauchiense extract gel formulation for 28 days did not show any negative effect, instead some biochemical parameters such as alanine aminotransferase (ALT and AST), low density lipoprotein (LDL), high density lipoprotein (HDL) and triglycerides were significantly (p < 0.05) affected positively. Conclusion These results indicate that the C. bauchiense ethyl acetate extract can be used safely for the treatment of some bacterial infections.